The Easiness in silico Drug Development against SARS-CoV-2 Protease using JAMDA - Broto Santoso; Ratna Yuliani (Konsorsium LPPM Perguruan Tinggi Muhammadiyah 'Aisyiyah (PTMA) Koordinator Wilayah Jawa Tengah - DIY, 2022)
Drug development can be accelerated and facilitated through the method of in silico by utilising a browser-based application. Universität Hamburg through the ZBH Centre for Bioinformatics has been giving full access to its applications until now. One of them is JAMDA. Forty-five flavonoids have been used as case studies of ligand binding affinity screening for five SARS-CoV-2 proteases. The 3D conformations of ligands and proteins were downloaded from the PubChem and RCSB databases, respectively. OpenBabel was used to combine multiple ligands to speed up the computation. It took at least 7.5 hours to complete the whole process using a single browser tab. Molecules of GC376 non-sulphonate, R8H, and 6”-O-acetylastragalin have top best scores than all investigated ligands. Their average scores ratio is 1.239, 1.234 and 1.188 respectively. PLIP predictions indicate that water molecules are actively involved in protein ligand interactions for four crystals of native and 6”-O-acetylstragalin on several proteins. This browser-based application is fast and easy to use but it is not recommended to use for novel compounds due to data privacy which is not guaranteed by the owner.